1997
DOI: 10.1073/pnas.94.8.4080
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic cells differentiate into both microglia and macroglia in the brains of adult mice

Abstract: Glial cells are thought to derive embryologically from either myeloid cells of the hematopoietic system (microglia) or neuroepithelial progenitor cells (astroglia and oligodendrocytes). However, it is unclear whether the glia in adult brains free of disease or injury originate solely from cells present in the brain since the fetal stage of development, or if there is further input into such adult brains from cells originating outside the central nervous system. To test the ability of hematopoietic cells to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
575
3
15

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 929 publications
(614 citation statements)
references
References 30 publications
21
575
3
15
Order By: Relevance
“…This second possibility challenges the idea that astrocytes are of neuroectodermal lineage, but agrees with the ®nding by Eglitis and Mezey (1997) that astrocytes of donor origin appear in mice subjected to bone marrow grafting.…”
Section: Origin From Neuroectodermal Cellssupporting
confidence: 77%
See 1 more Smart Citation
“…This second possibility challenges the idea that astrocytes are of neuroectodermal lineage, but agrees with the ®nding by Eglitis and Mezey (1997) that astrocytes of donor origin appear in mice subjected to bone marrow grafting.…”
Section: Origin From Neuroectodermal Cellssupporting
confidence: 77%
“…A study by Krall et al (1994) showed that ca 20% of microglial cells (mainly perivascular cells) were replaced by cells of donor origin 6±8 months after bone marrow transplant in mice; these results were in accordance with those reported by Kennedy and Abkowitz (1997). Finally, a recent paper (Eglitis and Mezey, 1997) con®rmed that transplant-derived cells colonize the CNS of bone marrow-chimeric mice; certain of the cells of donor origin were identi®ed as microglia, but surprisingly, some astrocytes were also found to be of donor origin.…”
Section: Origin From Primitive Hemopoietic Cellsmentioning
confidence: 99%
“…Bone marrow stromal cells or mesenchymal stem cells (MSCs) not only give rise to mesodermal lineage cells such as osteoblasts, chondrocytes, adipocytes, and muscle cells (4,13,29,55,33), but also adopt neuroectodermal cell fate. It has been shown that donor-derived neurons and astrocytes are found in host rodent brain following transplantation of rodent bone marrow (8,14,29,35). However, it is not known if transplantation of MSCs into the brain can be beneficial in treating neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, other studies have shown that stem cells residing in one tissue can differentiate into cell types of another tissue. For example, reserve stem cells derived from bone marrow can differentiate into neurons and glia (Eglitis and Mezey, 1997;Kopen et al, 1999), restore dystrophin expression in skeletal muscle (Gussoni et al, 1999), serve as a source of hepatic oval cells (Petersen et al, 1999), provide cells for neovascularization (Asahara et al, 1999;Kalka et al, 2000), and restore cartilage, bone, and fat (Pittenger et al, 1999;Prokop, 1997;Yoo et al, 1998). Conversely, stem cells derived from neural tissues (Bjornson et al, 1999) and muscle tissues (Jackson et al, 1999) can differentiate into blood.…”
mentioning
confidence: 99%